Developing local culture-based EFL reading materials for the 21st-century learning - Yeni Oktarina; Rita Inderawati; Ismail Petrus (Studies in English Language and Education, 2022)
The material specification is one aspect of teaching English at a vocational high school. Materials should be well-prepared to facilitate and promote students’ comprehension of concepts. This study aimed to develop instructional reading materials for Palembang – Tourism-Destination that are valid, practical, and potentially effective for students enrolled in a Travel Agent Study Program at one vocational school in Palembang, South Sumatera Province, Indonesia. The product was developed to meet the students’ needs. This research was a developmental study, with research phases including design, evaluation, and revision phases. Questionnaires, interviews, and reading comprehension tests were used to collect data. The data were analyzed quantitatively and qualitatively. A formative evaluation was conducted to determine the product’s validity, practicality, and potential impact. Experts evaluated the content, media, and instructional design for validity. The results indicated that the established product was extremely valid, scored an average of 3.65 for all evaluated elements. Practicality was rated highly in one-to-one and small-group evaluations, with average scores of 3.55 and 3.35. The results of the field test showed that the established texts had a high potential for impact, as 79.16 percent of students earned the required passing grade. As a result, it is reasonable to assume that the established product can be used in the classroom as the product for reading.